2020
DOI: 10.1186/s12911-020-01202-1
|View full text |Cite
|
Sign up to set email alerts
|

E-health literacy and associated factors among chronic patients in a low-income country: a cross-sectional survey

Abstract: Background: Chronic patients persistently seek for health information on the internet for medication information seeking, nutrition, disease management, information regarding disease preventive actions and so on. Consumers ability to search, find, appraise and use health information from the internet is known as eHealth literacy skill. eHealth literacy is a congregate set of six basic skills (traditional literacy, health literacy, information literacy, scientific literacy, media literacy and computer literacy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
68
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 54 publications
15
68
1
2
Order By: Relevance
“…Utilizing the Norman and Skinner (2006) scale for measuring self-perceived eHealth literacy (eHEALS) in a representative Israeli sample, Neter and Brainin (2012) found age and education differences between people with high and low eHealth literacy levels, so that the more literate were younger and more educated. Similar findings regarding demographic variables were found in other samples (Choi & Dinitto, 2013;Hoogland et al, 2020;Knapp et al, 2011;Shiferaw, Tilahun, Endehabtu, Gullslett, & Mengiste, 2020). Moreover, differences between high and low eHealth literates were found in information consumption practices and search outcomes, where search outcomes included contact with the attending physician, enhanced use of medical insurance, health behaviors, self-management of health needs, and understanding of the disease/condition (Neter & Brainin, 2012).…”
Section: Health Literacy Ehealth Literacy and Their Association With Health Outcomessupporting
confidence: 74%
See 1 more Smart Citation
“…Utilizing the Norman and Skinner (2006) scale for measuring self-perceived eHealth literacy (eHEALS) in a representative Israeli sample, Neter and Brainin (2012) found age and education differences between people with high and low eHealth literacy levels, so that the more literate were younger and more educated. Similar findings regarding demographic variables were found in other samples (Choi & Dinitto, 2013;Hoogland et al, 2020;Knapp et al, 2011;Shiferaw, Tilahun, Endehabtu, Gullslett, & Mengiste, 2020). Moreover, differences between high and low eHealth literates were found in information consumption practices and search outcomes, where search outcomes included contact with the attending physician, enhanced use of medical insurance, health behaviors, self-management of health needs, and understanding of the disease/condition (Neter & Brainin, 2012).…”
Section: Health Literacy Ehealth Literacy and Their Association With Health Outcomessupporting
confidence: 74%
“…Tangible outcomes could be adoption of health behaviors (Guo et al, 2021;Kim et al, 2018;e.g. Mitsutake, Shibata, Ishii, & Oka, 2016), healthcare utilization (Maroney et al, 2020) and ultimately health (or perceived health, see Shiferaw et al, 2020) though a recent review concluded that there are currently too few studies attesting on these associations (Neter & Brainin, 2019). eHealth literacy has been measured thus far mostly with eHEALS (Griebel et al, 2017;Neter & Brainin, 2019), though its shortfalls chiefly in assessing 'participative Internet' (i.e.…”
Section: Health Literacy Ehealth Literacy and Their Association With Health Outcomesmentioning
confidence: 99%
“…Smoking and excessive alcohol were not associated with eHEALS scores. The results were consistent with general surveys of Japanese adults, in which the eHEALS scores was not associated with smoking or alcohol consumption but were associated with physical activity [35,37]. This may be because the rates of habitual drinkers (470/6183, 7.6%) and current smokers (589/6183, 9.5%) were low in this study; thus, it is di cult to assess the association of eHEALS scores and drinking and smoking.…”
Section: Discussionsupporting
confidence: 87%
“…SRH knowledge might be considered part of health literacy [ 81 ]. The relevance of achieving (health) literacy relies on literacy to impact health knowledge, health status, and access to health services, in addition to income level, occupation, education, housing, and access to medical care [ 81 , 82 ]; all of them are “red spots” in the Latin-American region and contribute to the current humanitarian crisis. Meanwhile, health literacy has been shown to positively impact different health-related outcomes [ 83 , 84 ], and should be integrated in to national education initiatives.…”
Section: Discussionmentioning
confidence: 99%